The dilemmas of educational services for newly arrived immigrant students. A comparative study of models in Andalusia (ATAL) and Madrid (bridge classrooms) - Goenechea Permisán, Cristina; García Fernández, José Antonio; Jiménez Gámez, Rafael Ángel (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
This study compares Temporary Language Adaptation Classrooms (ATAL) in Andalusia and Bridge Classrooms (AE) in Madrid. Both programmes have been set up as a response to the needs of newly arrived foreign students who lack a proficient knowledge of the Spanish language. Despite the coincidence in their targets, their organizational and operational differences are an invitation to carry out this analysis where we reflect on the results obtained from different research projects in both regional communities. We particularly focus our analysis in four points that to our understanding form the basic dilemmas at the time of devising these types of classrooms that intend to enhance the language support measures for newly arrived foreign students: a) The number of hours that foreign students attend to language classes, i.e., how long they spend separated from the other students in his regular class group. b) The kind of support that they receive inside and outside the regular classroom. c) The curriculum to be covered in theses support classes. To what extent they are exclusively focused in linguistic aspects or if they also cover other contents from ordinary subjects. d) The role that original cultures and languages of the students have in the classroom. If they are taken into account as a support and basis or if they are ignored altogether.